Examination of the lipid profile, antioxidant capacity, and impact of Sida linifoliaL.extract on the liver and kidney functions of mice infected with malaria - Nicodemus Emeka Nwankwo; Osmond Oluchukwu Ugwu
The study aimed to investigate the impact of treatment with the ethanolic leaf extract of Sida linifolia(ELES) in malaria-infected mice and the effect of the extract on tissues and organs. Phytochemical screening was conducted, and the liver and kidney function parameters, lipid profile, antioxidant parameters, and electrolyte status were determined. From the findings of the study, tannins, saponins, flavonoids, steroids, and other phytochemicals were detected. The activities of alkaline phosphatase, aspartate aminotransferase, superoxide dismutase, and total protein, triacylglycerol, high-density lipoproteins, and electrolytes concentrations of the infected animals treated with different doses of the extract were significantly (p <0.05) higher compared to the untreated group (positive control). Conversely, the levels of creatinine, urea, total bilirubin, total cholesterol, low-density lipoproteins, and catalase activity of the treated groups were significantly (p <0.05) lower than those of the positive control. The malondialdehyde and reduced glutathione concentrations of the treated group showeda non-significant (p >0.05) difference compared to the positive control. Overall, these findings suggest that the ethanolic leaf extract of S. linifoliaexerted an antioxidant effect, but some perturbations in the electrolyte concentrations and the elevated levels of the liver enzymes could mean some potential stress to some tissues and the liver, so care should be taken in the administration of the agent.